PERCEIVED EFFECTIVENESS OF INDIGENOUS TECHNICAL KNOWLEDGE ON FISH PRODUCTION PRACTICES IN ASSAM - DEVI, RAJITA; SAHA, BISWARUP; PANDIT, ARUN; KASHYAP, DIPANJAN (Journal of the Inland Fisheries Society of India, 2021)
A total of 23 indigenous technical knowledge (ITK) on fish production practices in Nagaon district of Central Assam were documented. Pond preparation and renovation (22.22%), water quality management of fish pond (27.78%), stocking managment (16.67%), fish feeding management (33.33%) and disease and pest control constituted the major categories of indigenous technical knowledges. Scientific rationality, awareness and adoption among farmers regarding these ITKs were analysed and 17 rationale practices as perceived by the experts were studied further to examine their perceived effectiveness. The scientific rationale/operational principles behind 17 rational ITKs were also elucidated in this study. Farmers’ knowledge on a majority of selected ITK was good with more than 50% of the sampled farmers (51.25 to 84.50% per practice) were having awareness on 12 practices. Four practices were adopted by more than 50 % of the farmers. Of the 17 ITKs studied for effectiveness, 7 were perceived as highly effective by the farmers as well as experts from the particular location, implying that many indigenous practices were both rational as well as effective. This calls for more scientific intervention to validate the indigenous knowledge. Key words: Adoption, indigenous practices, perceived effectiveness, rationality, traditional knowledge